Overexpression of Endogenous Retroviruses and Malignancy Markers in Neuroblastoma Cell Lines by Medium-Induced Microenvironmental Changes - Wieland, Lisa; Engel, Kristina; Volkmer, Ines; Krüger, Anna; Posern, Guido; Kornhuber, Malte E.; Staege, Martin S.; Emmer, Alexander (Frontiers in Oncology, 2021)
Neuroblastoma (NB) is the commonest solid tumor outside the central nervous system in infancy and childhood with a unique biological heterogeneity. In patients with advanced, metastasizing neuroblastoma, treatment failure and poor prognosis is often marked by resistance to chemo- or immunotherapy. Thus, identification of robust biomarkers seems essential for understanding tumor progression and developing effective therapy. Here, we have studied the expression of human endogenous retroviruses (HERV) as potential targets in NB cell lines during stem-cell medium-induced microenvironmental change. Quantitative PCR revealed that relative expression of the HERV-K family and HERV-W1 ENV were increased in all three NB cell lines after incubation in stem-cell medium. Virus transcriptome analyses revealed the transcriptional activation of three endogenous retrovirus elements: HERV-R ENV (ERV3-1), HERV-E1 and HERV-Fc2 ENV (ERVFC1-1). Known malignancy markers in NB, e.g. proto-oncogenic MYC or MYCN were expressed highly heterogeneously in the three investigated NB cell lines with up-regulation of MYC and MYCN upon medium-induced microenvironmental change. In addition, SiMa cells exclusively showed a phenotype switching from loosely-adherent monolayers to low proliferating grape-like cellular aggregates, which was accompanied by an enhanced CD133 expression. Interestingly, the overexpression of HERV was associated with a significant elevation of immune checkpoint molecule CD200 in both quantitative PCR and RNA-seq analysis suggesting tumor escape mechanism in NB cell lines after incubation in serum-free stem cell medium.